Blockchain‐based electric vehicle charging reservation scheme for optimum pricing. (3rd June 2022) - Tanwar, Sudeep; Kakkar, Riya; Gupta, Rajesh; Raboaca, Maria Simona; Sharma, Ravi; Alqahtani, Fayez; Tolba, Amr
Summary: The adaptation of intelligent transportation system has evolved the quality of life of people with the huge demand for electric vehicles. Moreover, it becomes essential to schedule an electric vehicle for charging optimally. Therefore, this paper proposes a blockchain‐based electric vehicle charging reservation scheme for optimum pricing. It primarily aims to secure data transactions between electric vehicles and charging stations. It uses the communication channel as 5G to ensure ultra‐low latency and extremely high reliability. Furthermore, the proposed scheme uses a double‐auction mechanism to optimize the payoff for both electric vehicles and charging stations. The performance of the proposed scheme is evaluated by distinguishing it from the conventional networks such as 4G and LTE‐A. The performance parameters are considered profit and loss for electric vehicles, scalability, cost overhead for data storage, communication overhead for data transactions, and data storage cost. Results show that the proposed scheme is secure and achieves the optimized payoff for electric vehicles and charging stations compared with traditional approaches. Abstract : Novelty Statements Proposed a blockchain‐based EV charging reservation scheme for optimum pricing and used an IPFS data storage protocol to provide a cost‐efficient reservation scheme for EVs charging Implemented a double‐auction mechanism to optimize the payoff of EVs and CSs in the system. Performance evaluation of the proposed scheme has been analyzed using parameters such as profit and loss analysis for EVs, data storage cost, communication overhead for data transactions, scalability, and optimal payoff